A study of the influence produced by the dynamics of the working bodies of cotton-processing machines on the cotton fibre quality - Veliev, Fazil (Eastern-European Journal of Enterprise Technologies, 2021)
Cotton mass is considered as a compressible porous two-component medium, consisting of a mixture of cotton fibres and air included in the porous medium, which is essential in dynamic treatment processes and requires consideration when planning technological modes. It was found that the speed of sound in multicomponent media significantly decreases with an increase in the content of the gaseous component. With a certain content of components, it can become less than in each of the components separately. This is due to the fact that with an increase in the content of the gaseous component, the density of the medium increases insignificantly, and the compressibility of air sharply decreases in the pores. As a result of the research, it was found that the value of the dynamic change in the density of cotton raw materials can significantly exceed its density during static compression. This kind of influence can have both adverse and desirable effects on the primary stage of cotton processing. The dynamic characteristics of raw cotton as an object of mechanical technology were studied. The values of the speed of sound as a function of the density of cotton raw materials were determined on the basis of the theory of a two-component porous medium. The types of the dynamic compression curve of raw cotton have been established. Experimental studies on the compressibility of raw cotton are generalized. From the analysis of the cleaning processing of fibres and seeds on cleaning machines, it follows that when assigning a technological processing mode, it is necessary to comply it with the value of the sound speed for a given density of raw materials. It is necessary to avoid such rates of penetration of the working bodies into raw materials that are commensurate with the speed of sound at a given raw material density. This local dramatic increase in cotton media characteristics is a significant cause of fibre damage